ANALISIS SISTEM AKUNTANSI PIUTANG PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN KUPANG - Olivia Latumahina (P3M- Politeknik Negeri Kupang, 2022)
The purpose of this study was to determine the Accounts Receivable System at the Regional Water Company (PDAM) of Kupang Regency. The data were processed and analyzed using qualitative descriptive analysis. From the data results, it is known that the Accounts Receivable System implemented by PDAM Kupang Regency has been implemented properly because it is in accordance with the accounting system theory applied. However, the ability to collect receivables from PDAM Kupang Regency is still low so that the number of receivables increases every year. Because there is no clear picture of the party or section that records receivables. It is expected that the Regional Water Company of Kupang Regency can improve the existing system of receivable collection procedures and pay more attention to it carefully so that it can carry out the procedures for collecting receivables more optimally, so that it can have a good impact and can reduce high receivables in the future